ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA DI KELAS 2 SD IT BUNAYYA - Rohmah, Siti; Anggraeni, Dinnie; Haryani, Iis (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2023)
This research was conducted in class II SD IT BUNAYYA with the aim of finding out information about what factors cause students to have difficulty learning mathematics. This type of research uses a descriptive qualitative approach. The research design used was a case study. The subjects in this study were class II teachers and 5 class II students of SD IT BUNAYYA. The data collection instrument for this research was observation, interviews and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the discussion from this study indicate that 1) the difficulties experienced by class II students of SD IT BUNAYYA in learning mathematics, namely students having difficulty understanding concepts in the material of equivalent currency values, difficulties in arithmetic skills on division and multiplication material, difficulties in solving problems, especially in the form about story. 2) the factors that cause learning difficulties in mathematics consist of two factors (internal factors and external factors). Internal factors consist of weak intelligence, low student learning motivation, and also a lack of asking students to study mathematics, while external factors consist of inappropriate application of learning strategies and media and a lack of parental attention to student learning development.